Optimal configuration strategy of hybrid energy storage system on industrial load side based on frequency division algorithm. (June 2022) - Tang, Rongchuan; Xu, Qingshan; Fang, Jicheng; Xia, Yuanxing; Shi, Yun
Abstract: Electricity bills typically account for a large proportion of industrial users' production costs. Hybrid energy storage system (HESS), a high-performance energy storage method, has been widely used on the demand side. In the context of a two-part tariff system, the optimal configuration of battery-ultracapacitor HESS on the industrial load side realizes demand management and cost saving. Complete decoupling of load data promotes the full play to the advantages of batteries and ultracapacitors. Therefore, a VMD-ST-QF load frequency division strategy is proposed to decompose the chronological load curve into high-frequency and low-frequency components precisely. Depending on the results of frequency division, an optimal configuration strategy of HESS is established to minimize the net investment cost of energy storage. In this paper, the economic benefits of assembling energy storage on the industrial load side with four different configuration strategies are compared. The case study shows that the introduction of HESS based on the VMD-ST-QF strategy saves industrial users 5.26% of their total electricity cost and shortens the payback period of energy storage investment. Highlights: A VMD-ST-QF load frequency division strategy is proposed to decouple the load curve. Decoupling gives full play to the advantages of battery and ultracapacitor. An optimal configuration strategy of battery-ultracapacitor HESS is constructed. The introduction of HESS on load side increases the economic benefits for investors.